SAK EMKM Adoption in Online Shop Financial Recordkeeping: Penerapan SAK EMKM dalam Pencatatan Keuangan Toko Online - Ridha Tuahta Maharany Munthe; Heri Widodo (Indonesian Journal of Law and Economics Review, 2025)
General Background: Micro, Small, and Medium Enterprises play a central role in Indonesia’s economy and require reliable financial reporting to support sustainability. Specific Background: Many MSMEs, including online-based businesses, still apply simple cash-based records that do not follow accounting standards. Knowledge Gap: Empirical evidence on SAK EMKM-based financial recordkeeping in small online manufacturing businesses remains limited. Aims: This study examines accounting practices at Elmeera Hijab Online Shop and evaluates financial records aligned with SAK EMKM. Results: The findings show that existing records were limited to cash inflows and outflows and lacked structured financial statements; after adjustment, statements of financial position, income statements, and notes were prepared. Novelty: This study presents a contextual case of SAK EMKM application in an online shop with manufacturing activities. Implications: The results provide practical guidance for MSMEs to improve financial reporting quality and decision-making through structured SAK EMKM implementation. Keywords: SAK EMKM, Financial Recordkeeping, MSMEs, Online Shop Accounting, Financial Statements Key Findings Highlights: Financial records were initially limited to basic cash transactions. Structured statements were prepared following SAK EMKM guidelines. Human resource limitations constrained formal accounting practices.